Earnings Growth and Employment Creation : An Assessment of World Bank Support in Three Middle-Income Countries - World Bank (Washington, DC, 2012)
This assessment reviews earnings and employment outcomes in Colombia, Tunisia, and Turkey during 1998-2007, as well as five policy areas (the MILES framework) likely to affect those outcomes: macroeconomic conditions, investment climate, labor regulations, education, and social protection. Employment-related outcomes in the three countries were mixed, with notable progress in economic growth, earnings and poverty reduction, but not in the employment to- population ratio or unemployment rate. This underscores the desirability of focusing on the full set of employment-related variables Gross Domestic Product (GDP), poverty, employment, unemployment, and earnings - in an integrative fashion rather than just on employment when setting the objectives of Bank support. This focus will need better employment-related statistics, an area where the Bank can help further. Bank objectives in the three countries focused more on MILES components than on employment itself. Bank support in the three countries achieved differential progress in the individual MILES components, with the most progress on macro stabilization, followed in approximate order by progress on the investment climate, education, social protection, and labor taxation and regulations. The experience of the three countries illustrates how analytic and advisory activities can be the main instrument of support in those areas where progress in reform is difficult and the need for building engagement and consensus is critical.